Penerapan Manajemen Risiko Dalam Meminimalisir Pembiayaan Bermasalah Pada Pembiayaan Akad Rahn - Sukmawati, Sukmawati; Retna Anggitaningsih (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to determine the factors that cause the risk of problematic financing in rahn contract financing, the application of risk management in minimizing problematic financing in rahn contract financing, and efforts to handle problematic financing in rahn contract financing. This study is a qualitative study with a descriptive approach. The results of the study indicate that the factors causing the occurrence of problematic financing risk in rahn contracts are caused by two main factors, namely internal and external factors, the implementation of risk management is carried out comprehensively including 5C analysis (Character, Capacity, Capital, Condition, and Collateral) but which is often applied only 2C (Character and Capacity), and document verification, as well as routine monitoring, efforts to handle problematic financing that are applied include a family approach, re-survey of partner conditions, and the implementation of financing restructuring.